Supramolecular architecture of severe acute respiratory syndrome coronavirus revealed by electron cryomicroscopy - Neuman, Benjamin W; Adair, Brian D; Yoshioka, Craig; Quispe, Joel D; Orca, Gretchen; Kuhn, Peter; Milligan, Ronald A; Yeager, Mark; Buchmeier, Michael J (Journal of virology, 2006)
Coronavirus particles are enveloped and pleomorphic and are thus refractory to crystallization and symmetry-assisted reconstruction. A novel methodology of single-particle image analysis was applied to selected virus features to obtain a detailed model of the oligomeric state and spatial relationships among viral structural proteins. Two-dimensional images of the S, M, and N structural proteins of severe acute respiratory syndrome coronavirus and two other coronaviruses were refined to a resolution of approximately 4 nm. Proteins near the viral membrane were arranged in overlapping lattices surrounding a disordered core. Trimeric glycoprotein spikes were in register with four underlying ribonucleoprotein densities. However, the spikes were dispensable for ribonucleoprotein lattice formation. The ribonucleoprotein particles displayed coiled shapes when released from the viral membrane. Our results contribute to the understanding of the assembly pathway used by coronaviruses and other pleomorphic viruses and provide the first detailed view of coronavirus ultrastructure.